PERFORMANCE OF PARENTS FOR TRUE POTATO SEED ATTRIBUTES AT DEESA (GUJARAT) - Vaghela, K O; Patel, N H; Patel, R N; Patel, C K (Potato Journal, 2013)
Sixty eight crosses were made in line x tester design utilizing 17 female and 4 male parents of wide genetic base to ascertain the performance of parents for TPS attributes. Among these cross MS/ 91-1326 x EX/A-680-16 for berry set, MF-I x TPS-13 for seeds per berry and OP-1 x EX/A-680-16 for 100-seed weight were found promising. Parental lines Kufri Sutlej, JX-118, DP-9904, JTH/C-107 and MF-I were good females and all four testers were good males for TPS production.